The moderate physical exercise in reducing post-prandial blood glucose and increasing glut-4 protein serum on diabetic male wistar rat (Rattus norvegicus) - Dian Damayanti; Alex Pangkahila; I Wayan Weta (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2021)
Introduction: A moderate-intensity diet and exercise regimen is highly recommended as a non-pharmacological therapy, which can be used in type 2 diabetes mellitus. It can increase the GLUT-4 protein serum activity in the receptor of the muscle cell membrane. This research aimed to prove that moderate physical exercise was able to reduce post-prandial blood glucose and increase GLUT-4 protein serum on diabetic male Wistar rat (Rattus norvegicus). Methods: This research employed an experimental pre-test post-test control group design by using 26 diabetic male Wistar rats that were randomly selected. The first group without moderate exercise, the second group with moderate exercise. The measurement of post-prandial blood glucose and GLUT-4 protein serum was performed after 14 days of treatment. Results: The median of post-prandial blood glucose levels for the control group (P0) in pre-test was 177.00 mg/dl and in post-test was 168.00 mg/dl, moreover for the treatment group (P1) in pre-test was 158.00 mg/dl and in post-test was 157.00 mg/dl. Moreover, the median of GLUT-4 for the control group (P0) in pre-test was 8.97 ng/dl and in post-test was 9.34 ng/dl, and for the treatment group (P1) in pre-test was 8.44 ng/dl and in post-test was 9.38 ng/dl. The results of the analysis in both groups showed that there was no significant difference between the control group and the treatment group. Conclusion: It can be concluded that moderate physical training did not significantly reduce post-prandial blood glucose, and did not significantly increase GLUT-4 serum on diabetic male Wistar rat.